Working patriarchies? Police and criminal justice responses to domestic abuse in Scotland 1960–1990 - Donaldson, Anni (Kriminologijos studijos, 2022)
Post-war Scotland remained a deeply patriarchal country. Domestic abuse was common yet widely under-reported by the women it affected. This article argues that police and criminal justice agencies in Scotland 1960–1990 were ‘working patriarchies’ which created significant barriers to reporting. Oral history narratives from domestic abuse survivors, police and criminal justice professionals reveal deeply patriarchal workplaces and practices designed to maintain longstanding traditions of the patriarchal family. These inhibited reporting, denied women access to safety and justice in private life and contributed to women’s continuing inequality in post-war Scottish society.